2020
DOI: 10.3390/jcm9020346
|View full text |Cite
|
Sign up to set email alerts
|

The Coming Age of Flavonoids in the Treatment of Diabetic Complications

Abstract: Diabetes mellitus (DM), and its micro and macrovascular complications, is one of the biggest challenges for world public health. Despite overall improvement in prevention, diagnosis and treatment, its incidence is expected to continue increasing over the next years. Nowadays, finding therapies to prevent or retard the progression of diabetic complications remains an unmet need due to the complexity of mechanisms involved, which include inflammation, oxidative stress and angiogenesis, among others. Flavonoids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 136 publications
(147 reference statements)
0
40
0
1
Order By: Relevance
“…In the eighth week, antidiabetic effects of hesperetin at all doses were not significantly different from the normal control group. Flavonoid acted as an active antidiabetic compound triggered insulin production and reduced blood glucose levels (Al-Ishaq et al, 2019;Caro-Ordieres et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the eighth week, antidiabetic effects of hesperetin at all doses were not significantly different from the normal control group. Flavonoid acted as an active antidiabetic compound triggered insulin production and reduced blood glucose levels (Al-Ishaq et al, 2019;Caro-Ordieres et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols, flavonoids, and food rich-flavonoids also present lipid-lowering properties that could ameliorate lipotoxicity in diabetic kidney disease [241]. Recently, a study performed by Jayachandran et al demonstrated the capacity of isoquecertin to regulate lipid metabolism via AMPK pathway [196].…”
Section: Polyphenols Flavonoids and Nutraceuticalsmentioning
confidence: 99%
“…Flavonoids are abundant in food and beverages highly consumed by human population including fruits, vegetables, tea, cocoa or wine [ 42 ] and in global are the bioactive compounds more largely associated with a reduced risk of all-cause mortality, type 2 diabetes [ 43 , 44 , 45 , 46 ], CVD [ 36 , 47 ], obesity and its comorbidities such as non-alcoholic fatty liver disease (NAFLD) [ 48 , 49 , 50 ] and more recently they have been described as potential therapeutic agents against cognitive pathologies such as Alzheimer’s disease (AD) [ 42 , 51 , 52 ] or cerebrovascular alterations [ 47 ].…”
Section: Polyphenols and Metabolismmentioning
confidence: 99%
“…As other groups of flavonoids, flavonols have shown healthy effects. They exhibit anticarcinogenic, anti-inflammatory, and antioxidant activities but also anti-obesity and antidiabetic properties in animal models and in humans where flavonols consumption has been associated to a lower risk of type 2 diabetes [ 43 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 ]. Some flavonols inhibited carbohydrate absorption thus lowering postprandial blood glucose mainly through the inhibition of the α-glucosidase activity but also by inhibiting glucose transporters (GLUT2, SGLT1) or other enzymes such as maltase or saccharase [ 236 ].…”
Section: Flavonolsmentioning
confidence: 99%